A solar-like magnetic cycle on the mature K-dwarf 61 Cygni A (HD 201091) - VIDOTTO, ALINE (My University, 2016)
Context. The long-term monitoring of magnetic cycles in cool stars is a key diagnostic in understanding how dynamo generation and amplification of magnetic fields occur in stars similar in structure to the Sun. Aims. We investigated the temporal evolution of a possible magnetic cycle of 61 Cyg A. The magnetic cycle is determined from 61 Cyg A’s large-scale field over its activity cycle using spectropolarimetric observations and compared to the solar large-scale magnetic field. Methods. We used the tomographic technique of Zeeman Doppler imaging (ZDI) to reconstruct the large-scale magnetic geometry of 61 Cyg A over multiple observational epochs spread over a time span of nine years. We investigated the time evolution of the different components of the large-scale field and compared it with the evolution of the star’s chromospheric activity by measuring the flux in three different chromospheric indicators: Ca II H&K, Hα and Ca II infrared triplet lines. We also compared our results with the star’s coronal activity using XMM-Newton observations. Results. The large-scale magnetic geometry of 61 Cyg A exhibits polarity reversals in both poloidal and toroidal field components, in phase with its chromospheric activity cycle. We also detect weak solar-like differential rotation with a shear level similar to that of the Sun. During our observational time span of nine years, 61 Cyg A exhibits solar- like variations in its large-scale field geometry as it evolves from minimum activity to maximum activity and vice versa. During its activity minimum in epoch 2007.59, ZDI reconstructs a simple dipolar geometry which becomes more complex when it approaches activity maximum in epoch 2010.55. The radial field flips polarity and reverts back to a simple geometry in epoch 2013.61. The field is strongly dipolar and the evolution of the dipole component of the field is reminiscent of solar behaviour. The polarity reversal of the large-scale field indicates a magnetic cycle that is in phase with the chromospheric and coronal cycle.
Keywords: dynamo / stars: activity / stars: chromospheres / stars: magnetic field / stars: solar-type; dynamo / stars: activity / stars: chromospheres / stars: magnetic field / stars: solar-type